Pengaruh pemberian diet rendah karbohidrat tinggi lemak terhadap penurunan CO2 darah dan perbaikan respirasi pada pasien penyakit paru obstruktif kronik di Rumah Sakit Immanuel Bandung - Ruth R Wijaya; I Dewa Putu Pramantara; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2005)
Background: Lung diseases are one of the main health problems in Indonesia. Among the lung diseases, Chronic Obstructive Pulmonary Disease (COPD) is the 7th leading causes of death in Indonesia. The prevalence COPD tends to increase due to increasing smoking habit, industrialization, air pollution, and more elderly people. Diet regulation for COPD patients were mainly for energy consumption, and accurate proportion of carbohydrate and fat. Excessive carbohydrate intake will increase blood CO2.Objective: To evaluate the influence of low carbohydrate and high fat diet on the decrease of CO2 concentration and improving respiration in acute exacerbation of COPD.Methods: This is an experiment study, with pre and posttest design. The subjects were COPD patients who hospitalized due to acute exacerbation. The subjects must be conscious, no left heart failure, no coronary heart disease, no acute respiratory failure that need ventilator and hospitalized for minimum 7 days and could take oral diet.Results: Women, younger, and no smoking COPD patients had decreased blood CO2 offer low carbohydrate high fatty diet. All patients with this diet experience had improvement in their respiratory symptoms.Conclusion: Low carbohydrate high fat diet decreases blood CO2 in new acute exacerbation of COPD patients, no smoking women and younger patients. However, this diet improved respiratory symptoms for all patients who receive it.